ASEAN+3 bond market guide 2017 Philippines. (Metro Manila, Philippines Asian Development Bank, 2017)
The Philippine domestic bond market consists of short and long term bonds, mainly issued by the Government of the Philippines. The Philippine bond market is dominated by Treasury Bills and Treasury Bonds. Although the size of the Philippine corporate bond market is still small relative to government bonds, it has been growing rapidly over the years.On 3 June 2016, the Bangko Sentral ng Pilipinas (BSP) formally adopted an interest rate corridor (IRC) system as a framework for conducting its monetary operations. The IRC is a system for guiding short term market rates toward the BSP policy interest rate, which is the overnight reverse repurchase (RRP) rate.
Keywords: Financet -- Asia; Philippines -- Economic integration; Bonds -- Philippines -- Statistics; Electronic books